Clean Water Production Enhancement through the Integration of Small-Scale Solar Stills with Solar Dish Concentrators (SDCs)A Review - Yusof M.F.; Zainol M.R.R.M.A.; Sandu A.V.; Riahi A.; Zakaria N.A.; Shaharuddin S.; Aziz M.S.A.; Noor N.M.; Vizureanu P.; Zawawi M.H.; Ikhsan J. (MDPI, 2023)
disinfection; distillation; experimental study; integrated approach; performance assessment; pollutant removal; rural area; severe acute respiratory syndrome; water temperature; water treatment